PERAN CAMERA PERSON DAN PENERAPAN PENGAMBILAN GAMBAR DALAM PROGRAM ACARA DI TVRI SUMSEL - Geni Andrio; Nurul Azizah; Dimas Umboro Sumbar (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
The role of the camera person in the program at TVRI South Sumatra is very essential in creating adequate visual quality and supporting the content of the event. The camera person is responsible for taking images that are in accordance with the needs of the narrative and the goals of the program, by applying framing, lighting, and selection of the right angle of view. In addition, the camera person must also be proficient in using camera movement techniques such as pan, tilt, and zoom to follow the movement of the subject or direct the focus of the audience. In the context of program programs at TVRI South Sumatra, this role becomes more important because this television station often broadcasts cultural and local programs that require special sensitivity in filming in order to display the essence of the culture and tradition that is highlighted. With this role, the camera person contributes significantly to the presentation of programs. Furthermore, the application of shooting techniques such as close-up, medium shot, And wide shots should be done carefully to express emotions, show details, or provide an overall picture of the situation.The role of the camera person in the program at TVRI South Sumatra is very essential in creating adequate visual quality and supporting the content of the event. The camera person is responsible for taking images that are in accordance with the needs of the narrative and the goals of the program, by applying framing, lighting, and selection of the right angle of view. In addition, the camera person must also be proficient in using camera movement techniques such as pan, tilt, and zoom to follow the movement of the subject or direct the focus of the audience. In the context of program programs at TVRI South Sumatra, this role becomes more important because this television station often broadcasts cultural and local programs that require special sensitivity in filming in order to display the essence of the culture and tradition that is highlighted. With this role, the camera person contributes significantly to the presentation of programs. Furthermore, the application of shooting techniques such as close-up, medium shot, And wide shots should be done carefully to express emotions, show details, or provide an overall picture of the situation.